2005
DOI: 10.1007/s00018-005-5041-3
|View full text |Cite
|
Sign up to set email alerts
|

Aloe emodin decreases the ERK-dependent anticancer activity of cisplatin

Abstract: The present study describes the ability of an anthraquinone derivative aloe emodin (AE) to reduce the cytotoxic activity of the platinum(II)-based anticancer agent cisplatin toward murine L929 fibrosarcoma and C6 glioma cell lines. The protective effect of AE was demonstrated by MTT and crystal violet assays for cell viability, and involved supression of cisplatin-induced apoptosis and necrosis, as assessed by lactate dehydrogenase release and flow cytometric analysis of DNA fragmentation or phosphatidylserine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…In C6 glioma cells, GIT-27NO simultaneously upregulated JNK and ERK, whereas the activity of p38 was not affected. It was shown that strong activation of ERK1/2 in L929 cells induced by cisplatin led cells to apoptosis, and its suppression neutralized the antitumor potential of the drug (41). Therefore, up-regulated ERK1/2 could be the possible reason for preferential apoptosis of L929 cells on treatment with GIT-27NO.…”
Section: Discussionmentioning
confidence: 99%
“…In C6 glioma cells, GIT-27NO simultaneously upregulated JNK and ERK, whereas the activity of p38 was not affected. It was shown that strong activation of ERK1/2 in L929 cells induced by cisplatin led cells to apoptosis, and its suppression neutralized the antitumor potential of the drug (41). Therefore, up-regulated ERK1/2 could be the possible reason for preferential apoptosis of L929 cells on treatment with GIT-27NO.…”
Section: Discussionmentioning
confidence: 99%
“…And only in cytokine-activated cells these effects is observable. On the other hand, the same authors 97 also reported that aloe-emodin (20 mM) can slightly reduce the cytotoxicity activity of cisplatin in murine fibrosacroma L929 and rat glioma C6 cells. The inhibition of ERK kinase was believed to be a protective effect.…”
Section: Sensitization Activitymentioning
confidence: 90%
“…[42] The proportion of cells in various cell cycle phases were determined with Cell Quest Pro software (BD).…”
Section: Cell-cycle Analysismentioning
confidence: 99%